Impact of Artificial Intelligence and Robotics on Early Childhood Education: A Framework-Based Approach Utilizing the Five Big Ideas Model - Basma Rashed Alghufali (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
This paper aims at presenting an adapted framework based on the five big ideas, specifically designed to teach young children about artificial intelligence (AI) through the use of robotics. This study investigates the proposed system which emphasizes the utilize of mechanical autonomy and play-based learning to create AI available and empower engagement among youthful children who have not begun formal tutoring. In November (2022), the public release of (ChatGPT-3.5), a generative pre-trained transformer AI chatbot developed by OpenAI, made generative artificial intelligence widely accessible, requiring only an internet connection and a smartphone or computer. As a result, generative AI, particularly versions (ChatGPT-3.5) and -(4), experienced a notable increase in usage, prompting extensive discussions regarding its sustainable integration across diverse sectors, including education at all levels, from primary schools to universities. However, practical testing and evaluation in Early Childhood education are still relatively unexplored. The researcher has followed a comparative and analytical approach to figure out the similarities and differences in AI concepts between the original (K-12) educational system and the newly redesigned early childhood education framework. To provoke children intrigued, key concepts are displayed through intelligent with mechanical technology and robot role-play. This study has concluded that there are various advantages of introducing AI topics to young children, including enhanced creativity, theory of mind skills, and knowledge of AI. This paper too gives suggestions for age-appropriate points, narrating, and play-based instructing strategies. This system points to prepare analysts and teachers with procedures for effectively coordination initial AI instruction into early childhood classrooms. Educating AI in a formatively responsive way can offer assistance sustain youthful children’s interest toward and understanding of a progressively AI-driven world.